2015
DOI: 10.1017/s0029665115001329
|View full text |Cite
|
Sign up to set email alerts
|

Iterative development of an online dietary recall tool, INTAKE24

Abstract: Dietary intake is a complex behaviour to accurately measure (1) . Twenty-four hour recalls are a popular choice for dietary surveys as they are quick to administer, do not require the participant to be literate (2) and are less burdensome to complete compared to other dietary assessment methods (3) . Technology offers the potential to make dietary assessment more convenient, intuitive and engaging for users. It also ensures consistency of coding and significantly reduces the cost as nutritional output can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 3 publications
0
39
0
Order By: Relevance
“…These have previously been criterion-validated in a feeding study and also evaluated for convergent validity against weighed food diaries with children aged 18 months to 16 years and their parents (11,12) . Intake24 was developed through four cycles of user-testing and feedback (13) . Convergent validity testing of Intake24 against interviewer-led 24-h recalls found that the two methods yielded comparable estimates (14) ; however, the instrument has not yet been criterion-validated against objective measures of energy, nor has reliability been examined.…”
mentioning
confidence: 99%
“…These have previously been criterion-validated in a feeding study and also evaluated for convergent validity against weighed food diaries with children aged 18 months to 16 years and their parents (11,12) . Intake24 was developed through four cycles of user-testing and feedback (13) . Convergent validity testing of Intake24 against interviewer-led 24-h recalls found that the two methods yielded comparable estimates (14) ; however, the instrument has not yet been criterion-validated against objective measures of energy, nor has reliability been examined.…”
mentioning
confidence: 99%
“…Four consecutive 24-hour-web-based dietary recalls, including at least 1 weekend day, are collected within 7 days of each visit using INTAKE 24 57. Psychometric measures of eating behaviour are assessed at each visit using the Three Factor Eating Questionnaire-51,58 the Problematic Eating Patterns Scale (unpublished scale), Eating in the Absence of Hunger Scale,59 Intuitive Eating Scale-260 and the Binge Eating Scale 61…”
Section: Methodsmentioning
confidence: 99%
“…The involvement of skilled professionals in the collection and analysis of complex dietary data has both economic implications and implications for scalability. To address these issues a number of systems have been developed that replace an interviewer in the 24hour recall method with an online survey [9,31,32]. For researchers, such systems provide tools to administer surveys and collect dietary records from participants with a detailed breakdown of the foods and drinks consumed, to enable the estimation of energy intake and intakes of macro-and micro-nutrients.…”
Section: Online Dietary Assessment Surveysmentioning
confidence: 99%
“…Those challenges motivated us to develop a recommender system that extracts food associations in an automated manner [25]. The recommender algorithm was developed for Intake24, open-source dietary assessment system for conducting large-scale population 24-hour multiple-pass recall surveys online [31].…”
Section: Recommender Systemmentioning
confidence: 99%
See 1 more Smart Citation